Country Partnership Framework for the Republic of Paraguay for the Period FY19-FY23 - World Bank Group (World Bank, Washington, DC, 2019)
This document lays out the rationale for, and principal elements of, the World Bank Group (WBG) Country Partnership Framework (CPF) for Paraguay for FY19 to FY23. The proposed CPF is aligned with the core priorities of the new Paraguayan Administratio